The Absence of the N-acyl-homoserine-lactone Autoinducer Synthase Genes traI and ngrI Increases the Copy Number of the Symbiotic Plasmid in Sinorhizobium fredii NGR234 - Grote, Jessica; Krysciak, Dagmar; Petersen, Katrin; Güllert, Simon; Schmeisser, Christel; Förstner, Konrad U.; Krishnan, Hari B.; Schwalbe, Harald; Kubatova, Nina; Streit, Wolfgang R. (Frontiers in Microbiology, 2016)
Plant-released flavonoids induce the transcription of symbiotic genes in rhizobia and one of the first bacterial responses is the synthesis of so called Nod factors. They are responsible for the initial root hair curling during onset of root nodule development. This signal exchange is believed to be essential for initiating the plant symbiosis with rhizobia affiliated with the Alphaproteobacteria. Here, we provide evidence that in the broad host range strain Sinorhizobium fredii NGR234 the complete lack of quorum sensing molecules results in an elevated copy number of its symbiotic plasmid (pNGR234a). This in turn triggers the expression of symbiotic genes and the production of Nod factors in the absence of plant signals. Therefore, increasing the copy number of specific plasmids could be a widespread mechanism of specialized bacterial populations to bridge gaps in signalling cascades.